Initiating the development of a curriculum for South African adult critical care retrieval - Van Rensburg, Louis (Department of Medicine, 2026)
The interfacility transfer of critically ill patients is a crucial component of emergency healthcare in South Africa, necessitated by disparities in healthcare infrastructure, specialist availability, and geographic constraints. Emergency Medical Services (EMS) facilitate these transfers, often requiring specialised Critical Care Retrieval (CCR) teams. Despite its significance, there is no standardised CCR training in South Africa, leading to inconsistencies in provider competence and patient outcomes. Aim of the Study: This research sought to design and validate a contextually relevant and competency-driven curriculum for adult CCR in South Africa. The proposed curriculum aims to enhance the knowledge, clinical proficiency, and decision-making skills of EMS practitioners involved in critical care transport. Methods: A multi-methods approach was used across four phases: 1. Scoping Review: Local and international CCR curricula were analysed to identify best practices and essential competencies. 2. Retrospective Case Review: A three-year analysis of Western Cape EMS patient care records (2018–2020) provided insights into the characteristics and needs of CCR patients. 3. Qualitative Study: Semi-structured interviews with CCR experts and focus groups with EMS learners were conducted to explore training gaps and competency needs. 4. Delphi Study: A panel of 83 experts participated in an iterative consensus-building process to refine and validate curriculum content and learning objectives. Results: Findings revealed systemic deficiencies in EMS training for CCR, including inadequate exposure to critical care principles, ventilation strategies, interfacility transport physiology, and non-technical skills such as leadership and clinical decision-making. The final curriculum framework includes modules on intensive care principles, advanced patient monitoring, procedural interventions, transport logistics, and evidence-based best practices. The curriculum aligns with NQF Level 8 and incorporates blended learning methodologies, including high-fidelity simulations and supervised clinical exposure. Conclusion: This study presents the first structured and standardised CCR curriculum for South African EMS, bridging key knowledge and skill gaps while aligning with international best practices. Its implementation could professionalise CCR, establish it as a recognised EMS specialisation, and improve patient safety and outcomes. Future research should focus on implementation strategies, faculty development, and long-term evaluation of its impact on patient care and system efficiency.